Atmospheric electrical field measurements near a fresh water reservoir and the formation of the lake breeze. Issue 1 (1st December 2016) - Lopes, Francisco; Silva, Hugo Gonçalves; Salgado, Rui; Potes, Miguel; Nicoll, Keri A.; Harrison, R. Giles
Abstract : In order to access the effect of the lakes in the atmospheric electrical field, measurements have been carried out near a large man-made lake in southern Portugal, the Alqueva reservoir, during the ALqueva hydro-meteorological EXperiment 2014. The purpose of these conjoint experiments was to study the impact of the Alqueva reservoir on the atmosphere, in particular on the local atmospheric electric environment by comparing measurements taken in the proximity of the lake. Two stations 10 km apart were used, as they were located up- and down-wind of the lake (Amieira and Parque Solar, respectively), in reference to the dominant northwestern wind direction. The up-wind station shows lower atmospheric electric potential gradient (PG) values than the ones observed in the down-wind station between 12 and 20 UTC. The difference in the atmospheric electric PG between the up-wind and the down-wind station is 30 V/m during the day. This differential occurs mainly during the development of a lake breeze, between 10 and 18 UTC, as a consequence of the surface temperature gradient between the surrounding land and the lake water. In the analysis presented, a correlation is found between the atmospheric electric PG differences and both wind speed and temperature gradients over the lake, thus supporting the influence of the lake breeze over the observed PG variation in the two stations. Two hypotheses are provided to explain this observation: (1) The air that flows from the lake into the land station is likely to increase the local electric conductivity through the removal of ground dust and the transport of cleaner air from higher altitudes with significant light ion concentrations. With such an increase in conductivity, it is expected to see a reduction of the atmospheric electric PG; (2) the resulting air flow over the land station carries negative ions formed by wave splashing in the lake's water surface, as a result of the so-called balloelectric effect. These negative ions will form a space-charge density (SCD) that can reduce the atmospheric electric PG. A formulation is derived here in order to estimate the local SCD.